Public Spaces in Pulau Pasaran: Everyday Practices and Social Meanings in a Coastal Fishing Settlement - Nova Asriana; Martin Muljana; Guruh Kristiadi Kurniawan (Department of Architecture, Faculty of Engineering, Universitas Diponegoro, Indonesia., 2026)
Public space is not only a physical domain but also a cultural and social representation of collective urbanism, particularly in kampungs in Indonesia. It has grown densely due to the increasing of population and urbanisation, which has reduced the number of public spaces. This study is to investigate how public spaces in coastal kampung create function in everyday life and what social meanings for residents to attach them and how these spaces contribute to resilience, particularly fishing-based community in Pulau Pasaran, Bandar Lampung, Indonesia. This research employs a qualitative approach descriptively through collecting data by spatial observation and mapping public spaces practices identifying the characteristics of public spaces. The results are that public spaces in Pulau Pasaran are not defined by formal design but by everyday urbanism through everyday human practices. The characteristics are relational, multifunctional and adaptive to environmental change in a scarcity of public spaces. They help together to build living infrastructure for resilience to repurpose every inch of space for social or economic use.